2013
DOI: 10.1080/00219266.2013.821748
|View full text |Cite
|
Sign up to set email alerts
|

Digital technology to support students’ socioscientific reasoning about environmental issues

Abstract: Scientific expertise and outcomes often give rise to controversy. An educational response that equips students to take part in such discussions is the teaching of socially acute questions (SAQs). With SAQs, the understanding of uncertainty, risk and how knowledge is developed is central. This study explores the way in which students from different disciplines and different continents are brought together via a digital platform to explore SAQs about environmental issues (a green algae outbreak linked to release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…We also established that, compared to exchanges between within‐country groups, the web‐based exchanges between the Australian and French groups led to significantly greater increases in reasoning (for more details on these findings, see Morin et al, , p 164), and we argue that this was due to the difference between the viewpoints of the groups associated with different contextual exposure to the issue, and differences in underlying cultural presumptions, that had to be negotiated in the web‐based exchanges. We further argue that improvements in reasoning on particular dimensions of the S3R can be associated with aspects of the web‐based exchanges.…”
Section: Context Of the Investigationsupporting
confidence: 58%
See 3 more Smart Citations
“…We also established that, compared to exchanges between within‐country groups, the web‐based exchanges between the Australian and French groups led to significantly greater increases in reasoning (for more details on these findings, see Morin et al, , p 164), and we argue that this was due to the difference between the viewpoints of the groups associated with different contextual exposure to the issue, and differences in underlying cultural presumptions, that had to be negotiated in the web‐based exchanges. We further argue that improvements in reasoning on particular dimensions of the S3R can be associated with aspects of the web‐based exchanges.…”
Section: Context Of the Investigationsupporting
confidence: 58%
“…First, we observe in our study (see Figure ) that the majority of exchanges between groups in the forum involved justifications of arguments that refer to Habermas' three worlds. Moreover, following a previous publication of our results (Morin et al, ), Korsager and Jorde () used a similar scenario to ours, involving younger pupils (16–19 years old) from Canada, China, Norway, and Sweden discussing the climate change issue. They also observed that diverse types of knowledges are evident in exploratory talk in the course of construction of wikis, which do not appear in the final wiki.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Simonneaux and Simonneaux (2009) expanded SSR by adding two components: identifying risks/uncertainties and accounting for culture and ethical principles in decision-making (2009). Morin, Simonneaux, Simonneaux, and Tytler (2013) and Morin, Simonneaux, Simonneaux, Tytler, and Barraza (2014) further refined their model by incorporating argumentation and a focus on sustainability. We interpret the expansion of SSR by Simonneaux and Simonneaux (2009) as an attempt to account for greater diversity in student navigation of complex issues.…”
Section: Socio-scientific Reasoningmentioning
confidence: 99%